Pharaoh Ant, Monomorium pharaonis (Linnaeus) (Insecta: Hymenoptera: Formicidae) - J. C. Nickerson; Donny L. Harris; Thomas R. Fasulo (EDIS, 2004)
The ant, Monomorium pharaonis (Linnaeus), is commonly known as the Pharaoh ant. This ant is distributed worldwide, is one of the more common household ants, and carries the dubious distinction of being the most difficult household ant to control.  This document is EENY-290 (originally published as DPI Entomology Circular 256), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 2003.